The effectiveness of self‐care support interventions for children and young people with long‐term conditions: a systematic review. Issue 3 (8th June 2012) - Kirk, S.; Beatty, S.; Callery, P.; Gellatly, J.; Milnes, L.; Pryjmachuk, S.
Abstract Children's health policy has highlighted the need to develop self‐care programmes. However, there is a lack of evidence on which to base the development of such programmes. This paper reviews the published research on the effectiveness of self‐care support interventions for children and young people with asthma, cystic fibrosis and diabetes. A systematic search was conducted of a range of electronic databases, supplemented by searching the reference lists of retrieved papers and published reviews. Retrieved studies were assessed against quality and eligibility criteria by two independent reviewers. The results were narratively synthesized to examine the effectiveness of self‐care support interventions on health status, psycho‐social well‐being, condition‐related knowledge, health service use and participant satisfaction. The search strategy identified 4261 papers which were screened against the review inclusion criteria. A total of 194 papers were assessed as being potentially eligible for inclusion with 15 papers being judged as adequate to include in the review. There is strong evidence of the effectiveness of interventions that target children/young people; use e‐health or group‐based methods; that are delivered in community settings. There is no evidence that interventions that focus on parents alone or are delivered only in hospital settings are effective. While there is some evidence to inform the development of self‐care support programmes, there is a need for well‐designed trials of interventions that are feasible to transfer into real‐life settings and which involve parents and children in their development.